Analisis Kinerja Keuangan Menggunakan Metode Economic Value Added pada PT Elnusa Tbk Tahun 2018-2022 - Zulfikar; Amiruddin; Rahmat Aidil Adhan (Politeknik Negeri Samarinda, 2024)
This study aims to determine the financial performance of PT ELNUSA Tbk based on Economic Value Added (EVA) analysis for the 2018-2022 period. The analytical tool used in this study is Economic Value Added (EVA) which consists of Net Operating Profit After Tax (NOPAT), Invested Capital (IC), Weighted Average Cost of Capital (WACC) and Capital Charges (CC). The type of data used in this research is quantitative data using secondary data. Secondary data obtained in this study can be accessed through the sites www.elnusa.co.id and www.idx.co.id. The results of the analysis from this study stated that the financial performance of PT Elnusa Tbk using the Economic Value Added (EVA) method in 2018 amounting to Rp. 152,143, -, in 2019 amounting to Rp. 153,234, -, in 2020 it was Rp. 159,941, -, in 2021 it was Rp. 122,900, -, and in 2022 it is Rp. 227,624,-. The results of this analysis indicate that the company's financial performance is good and the company has succeeded in creating a positive EVA value.